Предмет: Алгебра,
автор: caxapok507
log^2 2 по основанию x - log 2 по основанию х - 6=0
Вообщем, выглядит это так:
log(снизу 2)^2 x-log(снизу 2)x-6=0
Извините, просто немного забыл, как правильно читать логарифмы.
Спасибо.
Ответы
Автор ответа:
0
Log(2)^2 x-log2 x-6=0
Log2 x=t
t^2-t-6=0
D=1+24=25
t1=(1+5):2=3
t2=(1-5):2=-2
Log2 x=3
X1=2^3=8
Log2 x=-2
X2=2^(-2)=(1/2)^2=1/4
Log2 x=t
t^2-t-6=0
D=1+24=25
t1=(1+5):2=3
t2=(1-5):2=-2
Log2 x=3
X1=2^3=8
Log2 x=-2
X2=2^(-2)=(1/2)^2=1/4
Похожие вопросы
Предмет: Физика,
автор: vinogradinka14
Предмет: Литература,
автор: nv5102616
Предмет: Алгебра,
автор: vladislav5moskvin264
Предмет: Математика,
автор: Аноним